The adaptive potential of hard winter wheat varieties - O. A. Dubinina; N. N. Vozhzhova (Аграрная наука Евро-Северо-Востока, 2016)
The article describes the parameters of ecological plasticity and stability of characteristic "productivity" in hard winter wheat. Under conditions of the Rostov region hard winter wheat varieties breeding All-Russian Research Institute of Grain Crops: Donskoy Yantar’, Aksinit, Kurant, Agat donskoy, Amazonka, Lazurit, Kristella, Kiprida, Oniks were studied with green manure fallow predecessor in 2010...2015. Variety Donchanka was used as standard. The studies revealed that the average yield in the trials ranged from 5.9 t/ha at variety Donchanka up to 7.2 t/ha at variety Lazurit. The maximum yield for the period of studies was observed at Aksinit (9.8 t/ha). The most stable variety is Kurant which has a low coefficient of variation (CV = 7.8%), and regression coefficient (bi = -1.4). A Kristella had the highest coefficient of variation among the studied varieties (CV = 23.9%). We define a linear regression coefficient (bi) which is less than 1. These genotypes form stable yields under adverse growing conditions. By the method of two-way analysis of variance on parameter "productivity" it was found that the dispersion of "genotype -environment" significantly exceeds the variance of error. Ffactual > Ftheoretical at the sources of variation "variety", "conditions" and "variety-condition". This suggests that varieties respond differently to changes in climatic conditions. In our experiment variety Donchanka was the least responsive; most responsive - variety Lazurit. Varieties Lazurit and Kurant are recommended to growing on the extensive background. Here the highest return could be obtained at the lowest cost.